HUBUNGAN KEMAMPUAN VISUAL SPASIAL DENGAN PEMAHAMAN KONSEP DENAH PADA PEMBELAJARAN IPAS SISWA KELAS III SEKOLAH DASAR DI KELURAHAN SUSUKAN JAKARTA TIMUR - Nidhia Salsabila Khalishah; Otib Satibi Hidayat; Uswatun Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between visual-spatial ability and map concept comprehension among third-grade elementary school students. This is a correlational study using a quantitative approach. The population in this study consists of all third-grade elementary school students in Susukan Subdistrict, East Jakarta, for the 2025/2026 academic year, totaling 520 students, with a minimum sample size of 84 students determined using the Slovin formula at a 10% margin of error. The sampling technique used in this study is simple random sampling. Data were collected through a multiple-choice test to measure students’ visual-spatial abilities and their understanding of map concepts. Data were analyzed using descriptive and inferential statistical analysis techniques, with hypothesis testing using Spearman’s Rank Correlation (ρ) because the data were non-normally distributed. The results of the study indicate a positive and significant relationship between students’ visual-spatial abilities and their understanding of map concepts, with a correlation coefficient of ρ = 0.728, which falls into the strong category. Keywords: visual spatial ability, map concept understanding, elementary school students